Effect of cyclodextrins on the complexation and transdermal delivery of bupranolol through rat skin - Babu R.J.; Pandit J.K. (My University, 2025)
Bupranolol (BPL) is a potent beta-blocking agent, the extensive first-pass metabolism (>90%) and rapid elimination half-life (1.5-2.0h) of this drug make it well suited to be developed as a transdermal delivery system (TDS). Hydroxypropyl βCD (HPβCD) and partially methylated βCD (PMβCD) were used as penetration enhancers for BPL. The formation of inclusion complex of BPL with these cyclodextrins (CDs) was characterized in solution and solid states by phase solubility, X-ray diffractometry and differential scanning calorimetry (DSC) analyses. The effect of CDs on the permeation enhancement of BPL through rat skin was studied using side-by-side diffusion cells and pH 7.4 phosphate-buffered saline (PBS). CDs were employed at different concentrations with 0.4% (w/v) BPL as well as with excess quantity of BPL (1.0%, w/v) that CDs could not complex all the BPL and the drug was in the form of an aqueous suspension. The permeation of BPL from its aqueous suspension (0.4%, w/v) significantly increased when CDs were used at low concentrations (up to 2 and 5%, w/v concentration for HPβCD and PMβCD, respectively) (P<0.01). At higher CD concentrations, the permeation of BPL decreased; and both CDs at 10% (w/w), showed similar flux values to that of control (no enhancer, P>0.05). The permeation of BPL from its 1.0% (w/v) aqueous suspension increased with increase in concentration of CD up to 10% (w/v) for HPβCD and PMβCD. At 10% (w/v) concentration of HPβCD and PMβCD, the flux of BPL from its 1.0% aqueous suspension increased 3.8- and 4.6-fold (P<0.01 and P<0.001, respectively). The permeation data of skin pretreatment with CDs indicate that HPβCD had no effect on the skin, whereas PMβCD significantly reduced the skin barrier for BPL, as shown by 1.7-fold increase in the flux by PMβCD pretreatment (P<0.001). Overall, both HPβCD and PMβCD were found to be suitable for improving the solubility and penetration enhancement of BPL. © 2003 Elsevier B.V. All rights reserved.